(untitled) (Clinics, 2013)
OBJECTIVE: Ficus deltoidea leaves have been used in traditional medicine in Southeast Asia to treat diabetes, inflammation, diarrhea, and infections. The present study was conducted to assess the genotoxicity and acute and subchronic toxicity of a standardized methanol extract of F. deltoidea leaves. METHODS: Sprague Dawley rats were orally treated with five different single doses of the extract and screened for signs of toxicity for two weeks after administration. In the subchronic study, three different doses of the extract were administered for 28 days. Mortality, clinical signs, body weight changes, hematological and biochemical parameters, gross findings, organ weights, and histological parameters were monitored during the study. Genotoxicity was assessed using the Ames test with the TA98 and TA100 Salmonella typhimurium strains. Phytochemical standardization was performed using a colorimeter and high-performance liquid chromatography. Heavy metal detection was performed using an atomic absorption spectrometer. RESULTS: The acute toxicity study showed that the LD50 of the extract was greater than 5000 mg/kg. In the subchronic toxicity study, there were no significant adverse effects on food consumption, body weight, organ weights, mortality, clinical chemistry, hematology, gross pathology, or histopathology. However, a dose-dependent increase in the serum urea level was observed. The Ames test revealed that the extract did not have any potential to induce gene mutations in S. typhimurium, either in the presence or absence of S9 activation. Phytochemical analysis of the extract revealed high contents of phenolics, flavonoids, and tannins. High-performance liquid chromatography analysis revealed high levels of vitexin and isovitexin in the extract, and the levels of heavy metals were below the toxic levels. CONCLUSION: The no-observed adverse effect level of F. deltoidea in rats was determined to be 2500 mg/kg.